Analisis User Experience Pada Game Mobile Legends dengan Menggunakan Metode System Usability Scale - Nanda, Meindita Andriano; Kusumodestoni, R. Hadapiningradja; Wibowo, Gentur Wahyu Nyipto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The most popular game today is a mobile game, because it can be played anytime and anywhere, in the case of Mobile Legend Bang-Bang which has been used by more than one million users. Mobile Legend is one of the MOBA (Multiplayer Online Battle Arena) games, MOBA games are online games that combine RPG (Role Playing Game) and RTS (Real Time Strategy) to test the user experience based on usability using the System Usability Scale (SUS) method. (SUS) is one of the usability testing methods to obtain significant analysis results, questionnaires are given to 100 respondents who have been selected based on active users of Mobile Legends Bang-Bang in order to get a representative score result. This study aims to e.valuate the experience and feelings of player users using the Game Experience Questionnaire (GEQ) instrument. GEQ only focuses on the user's experience and feelings while playing. The results of the GEQ based on three modules, namely the Core Module, Social Presence Module and Post Game Module, showed good results in each dimension, such as in the dimensions of Positive Affect, Competence, Immersion, Empathy and Positive Experience, proving that respondents enjoyed the game by feeling that they could finish the game easily and did not feel negative impacts. With the calculation of data obtained based on the score results calculated based on the calculation formula of the System Usability Scale method, if the score result is less than 68, Mobile Legend needs a more significant improvement in terms of its usability.